Anggapan Pestisida Sebagai Obat Bagi Petani Bawang Merah Di Kabupaten Solok Dan Konsekwensinya Pada Lingkungan - Yane Oktavia; Afrizal; Mahdi (Jurnal Niara, 2024)
Increasing shallot production in Lembah Gumanti District, Solok Regency, is very dependent on the use of pesticides. Farmers seem to view pesticides as plant healing medicines rather than dangerous poisons. This research aims to determine farmers' perceptions about pesticides, and farmers' behavior in using pesticides and their influence on public health risks. The research was conducted in Nagari Sungai Nanam, Lembah Gumanti District, Solok Regency. The research uses descriptive qualitative research methods combined with a quantitative approach. Data collection techniques using questionnaires and interviews with a sample of 98 shallot farmers were selected using simple random sampling. The research results show that the majority of farmers have a positive perception of pesticides, viewing them as poisons that are dangerous but beneficial if used according to the rules. Most farmers have positive behavior in terms of knowledge, attitudes and actions, such as choosing the type of pesticide, spraying time, paying attention to the weather, using personal protective equipment and disposing of pesticide packaging. Negative behaviors such as excessive dosage and high spraying frequency are still found. Farmers' positive behavior has a good impact on the environment, especially reducing the risk of poisoning. The impacts of pesticide use such as dizziness/nausea/skin irritation were never felt by respondents who used complete PPE (52%), and some always experienced these impacts (4%). The use of pesticides according to regulations has never had an impact on respondents (53%). The use of pesticides has quite an impact on health risks and the sustainability of environmentally friendly agriculture